2017
DOI: 10.4269/ajtmh.17-0267
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Is More Prevalent Than Iron Deficiency among Anemic Pregnant Women at the First Antenatal Visit in Rural South Kivu

Abstract: Anemia is common during pregnancy and is associated with poor outcomes. Objectives were not only 1) to determine the prevalence of anemia and iron deficiency (ID) but also 2) to identify other factors associated with anemia in pregnant women from South Kivu province, in the eastern Democratic Republic of Congo. Between December 2013 and March 2014, 531 women attending the first antenatal visit in their second trimester of pregnancy were recruited. Sociodemographic, clinical, and biological data were collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
2
8
1
Order By: Relevance
“…The levels of AGP in our study are similar to those previously noted in studies of pregnant women [2022], including another in Nepal [11]. In contrast to CRP, AGP normally decreases over pregnancy [10, 20], as our study also observed.…”
Section: Discussionsupporting
confidence: 91%
“…The levels of AGP in our study are similar to those previously noted in studies of pregnant women [2022], including another in Nepal [11]. In contrast to CRP, AGP normally decreases over pregnancy [10, 20], as our study also observed.…”
Section: Discussionsupporting
confidence: 91%
“…In South Kivu, ID does not seem to be common among women, regardless of pregnancy. 5,6 A similar low ID prevalence was also found in preschool children in the same area. 4,5 As mentioned previously, elsewhere IS has been associated with a higher risk of malaria during pregnancy 9 and a higher risk of morbidity and mortality due to infectious diseases, including malaria, among preschool children.…”
Section: Iron Supplementation In First Antenatal Visitsupporting
confidence: 67%
“…Characteristics of the women and others results are reported elsewhere. 6 More than a quarter of the study population were primigravidae and half were in their fourth or higher pregnancy. Nearly 38% (199/530) and 16.5% (86/522) reported fever and antimalarial treatment, respectively, within the previous 3 months, whereas 63.8% (336/527) reported sleeping under insecticide-treated mosquito net (ITN) the prior night.…”
mentioning
confidence: 99%
See 2 more Smart Citations